Passion, Trait Self-Control, and Wellbeing: Comparing Two Mediation Models Predicting Wellbeing - Briki, Walid (Frontiers in Psychology, 2017)
Research has found that passion and trait self-control represented key determinants of wellbeing. Yet, no study to date has attempted to investigate the mediating influences of trait self-control and passion for accounting for the relationships between passion, trait self-control, and wellbeing (dependent variable). Using different frameworks, such as the dualistic model of passion and the neo-socioanalytic theory, the present study proposed two mediating models, considering either trait self-control (model 1) or passion (model 2) as the mediating variable. Five hundred nine volunteers from the United States (326 females and 183 males; Mage = 31.74, SDage = 11.05, from 18 to 70 years old), who reported being passionate about a specific activity (e.g., fishing, swimming, blogging; Mpassion = 5.94, SDpassion = .89), answered questionnaires assessing harmonious and obsessive passion, trait self-control, and wellbeing (measured through hedonic and eudaimonic wellbeing scales). Preliminary analyses revealed that both models were significant (model 1: absolute GoF = .366, relative GoF = .971, outer model GoF = .997, inner model GoF = .973, R2 = 18.300%, p < .001; model 2: absolute GoF = .298; relative GoF = .980; outer model GoF = .997; inner model GoF = .982; R2 = 12.111%, p < .001). Correlational analyses revealed positive relationships between harmonious passion, trait self-control, and wellbeing, and no relationships of obsessive passion with trait self-control and wellbeing. Mediation analyses revealed that trait self-control significantly mediated the relationship between harmonious passion and wellbeing (i.e., partial mediation, VAF = 33.136%). Harmonious passion appeared to significantly mediate the positive effect of trait self-control on wellbeing; however, the size of the mediating effect indicated that (almost) no mediation would take place (i.e., VAF = 11.144%). The present study is the first to examine the relationships between passion, trait self-control, and wellbeing, and supports the view that trait self-control and harmonious passion represent not only adaptive and powerful constructs, but also key determinants of wellbeing. Implications for the study of passion, trait self-control and wellbeing are discussed.